Analisis Nilai Moral Keluarga dalam Film “Norma: Antara Mertua dan Menantu” Karya Guntur Soeharjanto: Kajian Pragmatik - Indrawati Indrawati; Hendrik Furqon; Rodli Rodli (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study aims to describe the representation of family moral values in the film Norma: Antara Mertua dan Menantu by Guntur Soeharjanto through a pragmatic analysis. The study employs a qualitative method with a descriptive-qualitative design. The data source is the film Norma: Antara Mertua dan Menantu, while the data itself consists of linguistic and non-linguistic elements including dialogue, utterances, narration, scenes, expressions, gestures, intonation, and character actions that represent family moral values. Data collection was conducted using listening and note-taking techniques, followed by a descriptive analysis using a pragmatic approach based on the context of the speech situation. The results reveal five forms of family moral value representation in the film: (1) parental support and blessing for a child's relationship, (2) responsibility and cooperation within the family, (3) care for parents, (4) a child's responsibility toward their parents, and (5) honesty and mutual forgiveness in family relationships. The findings indicate that the meaning of utterances in the film is understood not only through linguistic elements but also through the underlying context of the speech situation. Thus, the film Norma: Antara Mertua dan Menantu represents family moral values that serve as a medium for reflection and learning regarding the importance of communication, responsibility, care, and mutual respect in family life.